Analisis Pengaruh Penambahan Passive Grid Terhadap Turbulensi pada Wind Tunnel Skala Kecil: Passive Grid Addition Effect on Turbulence Analysis in a Small-Scale Wind Tunnel - Bima Heska Putra; Erwin; Slamet Wiyono (Jurnal Asiimetrik: Jurnal Ilmiah Rekayasa Dan Inovasi, 2023)
One of the problems encountered by a laboratory with a small-scale wind tunnel facility is that the wind tunnel can only produce limited wind speed to simulate fluid behavior that passes through a tested object. This problem caused the laboratory to be unable to analyze fluid behavior that passed through a tested object. In that case, scale modeling to analyze fluid behavior at a certain speed without having to reach the actual speed is needed. The purpose of this research is to prove the passive grid addition effect on turbulence in a small-scale wind tunnel. The test is done by capturing smoke movement through the test section with and without a grid. Then analyze the collected data with SynthEyes software. The wind speed variation used in this research is between 0.5 and 6.0 m/s. The result of this research is that the smoke flow characteristic in a wind tunnel without a grid tends to be laminar flow, and the smoke flow in a wind tunnel with a grid tends to be turbulence flow. Smoke flow characteristics with a grid are still too far from smoke flow characteristics without a grid with the highest speed variation.